TESTING A TELEPHONIC ADVANCE CARE PLAN PROGRAM: A FEASIBILITY STUDY. (11th November 2018) - Tkatch, R; Draklellis, J; Maycroft, J; Schaeffer, J; Martin, T
Abstract: The gap between the health care that individuals receive at the end of life versus the care they would have preferred could be significantly reduced with prior completion of an Advance Care Plan (ACP). However, many individuals, including older adults, do not have an ACP. The purpose of this ACP study was to test the feasibility of a telephonically supported ACP-related discussion for older adults with a range of health status as part of a broader population health management program. Various current ACP models were considered in designing the study, which was intended to gauge interest and identify resources that may be helpful in having ACP conversations. Ten individuals participated in the research laboratory component and a debrief session afterwards. All interviews were audio and video recorded. Participants were open to having ACP conversations telephonically and having education provided, most reported they would not see a difference between a phone versus in-person discussion (n=8). Overall, participants reported the conversations elicited feelings of confidence, reassurance, and calmness. Only two participants reported feeling overwhelmed from the conversation. When asked whether they had a health advocate, all said yes and reported their intentions to speak with their health advocate in the near future. Future research should include a larger sample size and the use of a survey. This research provides data demonstrating the value of a telephonic ACP- related discussion as part of a population health program.